Language, literacy, and social change in Mongolia : traditionalist, socialist, and post-socialist identities - Marzluf, Phillip P. (My University, 2018)
Language, Literacy, and Social Change in Mongolia is the first full-length treatment of literacy in Mongolian. Challenging readers’ assumptions about Central Asia and Mongolia, this book focuses on Mongolians’ experiences with reading and writing throughout the past 100 years. Literacy, as a powerful historical and social variable, shows readers how reading and writing have shaped the lives of Mongolians and, at the same time, how reading and writing have been transformed by historical, political, economic, and other social forces.
Citation: Marzluf, P. (2018). Language, literacy, and social change in mongolia : Traditionalist, socialist, and post-socialist identities (Contemporary central asia: societies, politics, and cultures). Lanham: Lexington Books.